KARAKTERISTIK PERUSAHAAN DAN PENGUNGKAPAN MODAL INTELEKTUAL: PERUSAHAAN-PERUSAHAAN DI INDONESIA TAHUN 2015 - Yogi Arief Saputro; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2017)
This empirical quantitative study seeks to examine the influence of company’s characteristics on intellectual capital disclosure. They consist of type of industry, leverage, listing age, and corporate governance attributes (ownership concentration and type of external auditor). Data were gathered from the annual reports of 82 publicly listed companies in Indonesian Stock Exchange in 2015. This study uses a stratified random sample of all companies listed in Indonesian Stock Exchange as the population. The 82 samples chosen based on their type of industry; 41 companies were chosen from high-tech industry and 41 companies were from low-tech industry. Data collection is limited to one year and only from annual reports. Multiple regression statistics analysis results reveal that high-tech and knowledge-intensive companies disclose more information about intellectual capital than low-tech companies do. Companies audited by big-four auditors also disclose more information than those without big-four auditors. Ownership concentration has negative significance association with the extent of intellectual capital disclosure. Level of leverage and listing age did not influence the occurrence of intellectual capital disclosure.